The X‐ray crystal structure of human endothelin 1, a polypeptide hormone regulator of blood pressure. Issue 1 (3rd January 2019) - McPherson, Alexander; Larson, Steven B.
Abstract : The structure of endothelin in the unbound state has been determined using X‐ray diffraction data that were collected in 1992. The crystals exhibit higher symmetry than is in fact present, and they are significantly twinned. There is a dimer containing a pseudo‐twofold axis in the asymmetric unit. Abstract : Human endothelin is a 21‐amino‐acid polypeptide, constrained by two intra‐chain disulfide bridges, that is made by endothelial cells. It is the most potent vasoconstrictor in the body and is crucially important in the regulation of blood pressure. It plays a major role in a host of medical conditions, including hypertension, diabetes, stroke and cancer. Endothelin was crystallized 28 years ago in the putative space group P 61 22, but the structure was never successfully solved by X‐ray diffraction. Using X‐ray diffraction data from 1992, the structure has now been solved. Assuming a unit cell belonging to space group P 61 and a twin fraction of 0.28, a solution emerged with two, almost identical, closely associated molecules in the asymmetric unit. Although the data extended to beyond 1.8 Å resolution, a model containing 25 waters was refined to 1.85 Å resolution with an R of 0.216 and an R free of 0.284. The disulfide‐constrained `core' of the molecule, amino‐acid residues 1–15, has a main‐chain conformation that is essentially the same as endothelin when bound to its receptor, but many side‐chain rotamers are different. The carboxy‐terminal `tail' comprising amino‐acid residues 16–21 is extended as when receptor‐bound, but it exhibits a different conformation with respect to the `core'. The dimer that comprises the asymmetric unit is maintained almost exclusively by hydrophobic interactions and may be stable in an aqueous medium.